Recursos didáticos para o processo de ensino-aprendizagem de solos no ensino fundamental - Oliveira, Alexandre Nicolette Sodré (2017)
The school has an important social role, not only as a space for the dissemination of knowledge, but also for the formation of a critical and responsible spirit on the issues of our time. One of these important issues is the environmental agenda, more particularly on the rational use of land, which, despite its fundamental relevance for the sustainability of the planet, has not received due attention from pedagogical documents and teaching practice, often resulting in a superficial, mechanical and mistaken learning. Thus, it can be seen that the didactic resources used by the teachers have not been able to awake in the student the interest about the importance of the soil and its conservation, as well as the content of soils in textbooks is treated in a superficial, light and even with outdated and wrong concepts. Therefore, we seek with the research to answer the following problem: What alternative resources can be used as a way to make the teaching-learning process of soils in Elementary School feasible? The general objective was to investigate the use of didactic resources as a way to increase understanding of the soil, sensitizing students to the various forms of soil degradation and making them aware of the importance of their conservation in order to make feasible the teaching-learning process of this soil in Elementary School. The work was developed in the Municipal Schools Abílio Alencar and Solange Nascimento, located in the rural area of Manaus. The subjects of the research were 116 students distributed in four classes of 6th grade. Also four professors, being two of the discipline of Sciences and two of Geography, making a total of 120 participants. The procedure of the action research with a qualitative approach was used. We made use of audiovisual resources on the theme of soil and the strategy of field practice through the natural didactic resource of a soil profile and the green environment of the interior and surroundings of the schools. The data collection was done through the application of questionnaires and semi-structured interviews. The results indicate a significant increase and improvement of learning about the subject, besides contributing to raise awareness and sensitize students to the sustainability of the soils of our region.